Early detection of anastomotic leakage after pancreatoduodenectomy with microdialysis catheters: an observational Study. Issue 6 (June 2022) - Lindholm, Espen; Bergmann, Gisli Björn; Haugaa, Håkon; Labori, Knut Jørgen; Yaqub, Sheraz; Bjørnbeth, Bjørn Atle; Line, Pål-Dag; Grindheim, Guro; Kjøsen, Gisle; Pischke, Søren Erik; Tønnessen, Tor Inge
Abstract: Background: Microdialysis catheters can detect focal inflammation and ischemia, and thereby have a potential for early detection of anastomotic leakages after pancreatoduodenectomy. The aim was to investigate whether microdialysis catheters placed near the pancreaticojejunostomy can detect leakage earlier than the current standard of care. Methods: Thirty-five patients with a median age 69 years were included. Two microdialysis catheters were placed at the end of surgery; one at the pancreaticojejunostomy, and one at the hepaticojejunostomy. Concentrations of glucose, lactate, pyruvate, and glycerol were analyzed hourly in the microdialysate during the first 24 h, and every 2–4 h thereafter. Results: Seven patients with postoperative pancreatic fistulae (POPF) had significantly higher glycerol levels (P < 0.01) in the microdialysate already in the first postoperative samples. Glycerol concentrations >400 μmol/L during the first 12 postoperative hours detected patients with POPF with a sensitivity of 100% and a specificity of 93% (P < 0.001). After 24 h, lactate and lactate-to-pyruvate ratio were significantly higher (P < 0.05) and glucose was significantly lower (P < 0.05) in patients with POPF. Conclusion: High levels of glycerol in microdialysate was an early detector of POPF. The subsequent inflammation was detected as increase in lactate and lactate-to-pyruvate ratio and a decrease in glucose (NCT03627559).